An Investigation into Moisture Content of Textile Fabrics: Effects of Blending Ratio, Drying Temperature, Curing Time, Dyes, Detergents, and Softeners - Nguyen, Tuan Anh; Luong Thi , Ngoc Phuong; Tran Thi , Anh Tuyet (Journal of Technical Education Science, 2025)
The moisture content of textile fabrics plays a critical role in determining the quality and performance of garments, directly affecting their durability, comfort, and overall suitability for different end uses. Understanding how moisture content varies across textile types is essential for both manufacturers and consumers, as it impacts wearability, maintenance, and product longevity. This study develops into the primary factors that influence moisture content in a variety of fabrics, including the origin of the material, weave structure, environmental temperature, drying duration, and the effects of chemical agents like detergents and fabric softeners. Through the controlled experiments, the authors assessed the variables influence moisture content under diverse conditions. The results underscore the importance of fabric composition, with natural fibers like cotton exhibiting higher moisture content compared to synthetic counterparts. Temperature and humidity also play a significant role, as do variations in drying time. Additionally, chemical treatments, particularly the use of detergents and softeners, were found to alter the moisture levels, with noticeable differences depending on the type of fabric treated. These findings offer valuable insights for the textile industry, presenting strategies to optimize moisture content during production and processing. Accordingly, manufacturers can enhance garment quality while promoting sustainable resource utilization, thereby benefiting both businesses and consumers.